Femenine Stereotype in 140 Characters. Approach to the Hillary Clinton Campaign On Twitter - López-Hermida Russo, Alberto (2019)
This research exposes the use of stereotype of women in the first month of campaign on former First Lady Hillary Clinton’s twitter account and how the candidate takes advantage of resources. After reviewing the 191 published from April 12 until May 12 2015, the tools used by the frontrunner and her staff while she seeks to earn the vote of the American citizens will be presented to the reader.